Ekonomi Pembangunan Terhadap Pengangguran di Provinsi Jambi - Afrizal Afrizal (Journal Development, 2014)
Unemployment in developing countries such as Indonesia, the economic development of this country as a growing number of unemployment is a problem that is more complicated and more serious than the problem of changes in income distribution are less profitable low-income residents Unemployment in Jambi Province has reached tens of thousands of people is an urgent problem that must be solved because of the impact of unemployment it would be very dangerous to the social order of life. It is a fact that various social evils such as theft / muggings/robberies, prostitution, Jula buy children, street children and others merupakandampakdaripengangguran.